English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

algebra 2

2007-01-21 09:52:22 · 4 answers · asked by rh 2 in Science & Mathematics Mathematics

4 answers

-3(x-2) = 5(2x + 1) first distribute..
-3x + 6 = 10x + 5 next combine like terms
6 - 5 = 10x + 3x simplify
1 = 13x
x = 1/13

2007-01-21 09:57:22 · answer #1 · answered by Anonymous · 0 0

-3(x-2)=5(2x+1)
-3x + 6 = 10x + 5
-3x - 10x = 5 -6
-13x = -1
x = 1/13
><

2007-01-21 18:00:25 · answer #2 · answered by aeiou 7 · 0 0

-3(x-2)=5(2x+1)
-3x+6= 10x+5
6=13x+5
13x=1
x= 1/13

2007-01-21 17:56:32 · answer #3 · answered by      7 · 0 0

x = 0

If x = 0 then the first term becomes 6 (-3 X -2) as does the second.

2007-01-21 18:02:08 · answer #4 · answered by David A 5 · 0 0

fedest.com, questions and answers